Gestão da saúde e política de humanização na Amazônia brasileira - Almeida, Simone Lopes de (2013)
The Humanization of Health Policy (NHP) are gradually gaining notoriety both in academic discussions, as in level of intergovernmental decision. The same comes as policy defined in SUS, which runs through the different actions and management levels from the inclusion of managers, health workers and users in search of changes in the model of care and management from the autonomy and the role of these subjects, co-responsibility and the establishment of supportive links, building networks of cooperation and collective participation in the management process .. Was sought through the research literature on the contributions that attest to the importance of politics Humanization of Health, particularly its adoption at the municipal level, as a policy device changes, focused on participative management. This condition means suitable for the identification and measurement of local health problems, promoting the adoption of social protection appropriate to the context it is intended. What was the motive for this study is the observation that, despite the enormous importance of this subject together with your essential practice in health management, in the case of the Municipality of Caracaraí-RR, where this subject is still tentatively treated in discussions of the Municipal Council Health (CMS), the Municipal Health Plan and Management Report this city, but now appearing a bit more in terms of Municipal Health Conference, as evidenced by the case study underlying this thesis. This study is developed based on the logic that health management should be participatory, reaching the triple include: managers, workers and users, each with its focus on the needs and requests. The same has as objective to identify what the place of PNH in health management in a small city in the Brazilian Amazon as well as meet and discuss in / congruence between what advocates PNH and health management, in order to identify the presence or absence interconnection there between. It is proposed that the living conditions of social groups in the territories define the context of their local problems, needs and dissatisfactions. These conditions of existence can be good or bad, and change for better or worse, depending on the participation of government institutions and the population. Thus, the relevance of PNH as a management tool, and from its methods, guidelines and devices in the dynamics of SUS that works: equitable, democratic and participatory.